Causation and Divine Agency - Ganssle, Gregory E. 1956- (2023)
God's regular causal activity is traditionally held to include his creation of the world, his conserving all created things in being and his concurrence with the causal activities of finite causes. Divine causation requires that God is an agent. In this paper, I apply E. J. Lowe's view of human agency to God. This application requires certain adjustments. Lowe takes it that when a person acts for reasons, these reasons are lacks of some kind. I argue that his account can apply to God if we think of the reasons for God’s action as connected to purposes rather than to needs.